Mechanical forces and Hidradenitis Suppurativa - Boer, Jurr; Jemec, Gregor B.E. (Experimental dermatology, 2021)
The mechanism by which inflammatory skin disease forms localized patterns of lesions is poorly understood. Hidradenitis suppurtiva (HS) is strikingly located to intertriginous areas. These areas are subject to considerable mechanical stress (friction, pressure and shear forces). Koebner phenomenon (KP) describes the appearance of typical skin lesions of a pre‐existing dermatosis on previously clear skin following trauma, such as friction, pressure and more often penetrating injury with subsequent scarring. Striae distensae (SD) are a form of dermal scarring and can be considered as a form of inflammation‐driven dermal disarray. Ectopic HS lesions may occur as KP due to trauma and locally increased susceptibility consisting of either altered mechanical qualities or inflammation. SD and mechanical stress may thus provide a model for the development of lesions. In the absence of an (animal) model or experiment, two patients are described who show HS (‐like) lesions along co‐localized with SD. The suggested two‐hits model may be necessary for the development of KP in HS, that is that the general susceptibility, conferred by obesity, requires a local susceptibility factor to result in ectopic lesions. Ultimately, if ectopic HS lesions are considered true HS lesions it may be speculated that similar interaction occurs in the naturally stressed skin areas offering a possible explanation of the localized pattern of the disease.